1993
DOI: 10.1007/bf00216832
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure of NKG5, a human NK and T cell-specific activation gene

Abstract: We reported previously the isolation of a cDNA clone, designated NKG5, encoding a secreted protein that is expressed only in natural killer and T cells and is strongly upregulated upon cell activation. In this report we have isolated the NKG5 gene from a human placental genomic library and sequenced the gene and two kilobases of 5'-flanking DNA. Comparison with the cDNA sequence reveals that the NKG5 gene consists of five exons and four introns. Intron 1 contains a DNA segment that was reported to occur as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…The five exons/four introns structural feature is conserved between the catfish NK-lysin gene and the NKG5 splicing variant of human granulysin (Fig. 3) [36].…”
Section: Cmentioning
confidence: 99%
“…The five exons/four introns structural feature is conserved between the catfish NK-lysin gene and the NKG5 splicing variant of human granulysin (Fig. 3) [36].…”
Section: Cmentioning
confidence: 99%
“…6). Only a few NK-lysin genes have been reported, but the five exons/four introns structural feature is conserved between the catfish gene and the human gene (Houchins et al, 1993). However, in humans, alternative splicing of granulysin gene led to the identification of two isoforms of granulysin referred to as NKG5 and 519.…”
Section: Genomic Sequencing Of the Three Types Of Nk-lysin Genesmentioning
confidence: 99%
“…The NK-lysin gene was initially cloned and characterized from humans, but its significance was unrealized until its orthologue was identified from porcine natural killer cells and cytotoxic T lymphocytes as an antimicrobial peptide (Manning et al, 1992;Houchins et al, 1993;Andersson et al, 1995). In recent years, extensive research has been conducted for the analysis of structure and antimicrobial activities of NK-lysin (Stenger et al, 1998;Ernst et al, 2000;Gansert et al, 2003;Jacobs et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous observations, using Cryptococcus neoformans, which is one of the most common lifethreatening fungal infections in patients who have compromised cell-mediated immunity, including AIDS (10 -12), indicated that granulysin is required for the CD8 T lymphocyte-mediated direct antifungal activity (13). The granulysin (519) gene is also constitutively expressed in NK cells (14), and in fact was cloned as NKG5 (15,16), and NK cells constitutively express granulysin transcripts; consequently, we felt that granulysin was the likely mechanism for the NK cell-mediated antimicrobial activity.…”
mentioning
confidence: 99%